English Reading Strategies Used by Secondary-Level Students - Kandel, Uma (Journal of NELTA Gandaki, 2024)
This paper presents an analysis of students' strategies for reading English texts. The narrative inquiry research design was used to study four secondary-level students' experiences of different reading strategies of English texts. The findings show that the students use different cognitive and metacognitive strategies to understand the texts according to their level of reading engagement. They monitor their plans and evaluate their understanding while reading. This study found that reading silently and reading aloud, using previous knowledge while reading new texts, rereading and summarizing the texts, and solving problems are the main strategies used in reading English texts. This study reports that engaged readers use diverse strategies; however, struggling readers use limited strategies. The use of multiple strategies in the reading of English texts helps students better for their achievements and engagement in reading. The study shows that teacher support is important in using strategies because teachers can help students in selecting appropriate reading strategies. This study will be important for English language learners, teachers, educators, researchers, and motivators for future student-centered pedagogical approaches to transform teaching and learning experiences into EFL classrooms.